Academic Goals and Aspirations of the Indigenous Students - Gaite, Cristo Rey (Journal of Interdisciplinary Perspectives, 2025)
This study investigated the educational experiences of Indigenous Filipino students at a Philippine state university. The study aimed to provide narratives of their lived experiences in their academic goals and aspirations. The researcher employed Interpretative Phenomenological Analysis (IPA) and utilized Indigenous Standpoint Theory to ensure that the perspectives and voices of Indigenous students were heard. Data were gathered through in-depth interviews and focus group discussions and analyzed using key themes and subthemes. The study highlights the significance of education in fostering social mobility and enhancing personal and community empowerment. It also highlights the role of social capital in supporting indigenous youths' efforts to pursue higher education. The participants suggested several changes to university services to support Indigenous students, including creating an Indigenous Student Organization and a cultural awareness program, establishing Indigenous scholarships, and incorporating cultural topics into university orientations.